Growth monitoring and promotion services utilization and associated factors among children less than two years of age in Digelu Tijo district, south central Ethiopia - Dereje Girma; Derese Teshome; Yealamwork kerie; Abdene Weya Kaso; Muhammedawel Kaso (Elsevier, 2023)
Background: Growth monitoring and promotion(GMP) appear to be a prerequisite for good child health. Thus, this study assessed GMP utilization and associated factors among children less than two years in rural communities of Digelu Tijo district, Ethiopia, 2018. Method: We conducted a community-based cross-sectional study design to assess growth monitoring and promotion service utilization and its associated factors among children less than two years in rural communities of Digelu Tijo district, South Central Ethiopia. Multivariate logistic regression was used to determine the presence of statistically significant associations between the GMP utilization and independent variables at p-value <0.05 and Adjusted odds ratio (AOR) values with a 95% Confidence Interval(CI). Results: The overall utilization of GMP service in the study area was 32.8%. Factors such as children aged 0-11 months old (AOR = 3.59, 95% CI: 2.42, 5.31), mothers/caregivers whoever used a family health card (AOR:2.65, 95% CI: 1.77,3.96), utilized postnatal care services (AOR:1.54, 95% CI: 1.03,2.31), visited health facilities only for GMP (AOR:2.23, 95% CI: 1.48, 3.36), and discussed on child growth with husband (AOR:3.29, 95% CI: 2.23, 4.83) were significantly associated with utilization of GMP service. Conclusion: We found that overall GMP services utilization was low in the study area. GMP service utilization was found to be significantly associated with child age, visiting health facilities for GMP service only, and discussing child growth with husband. Thus, designing an intervention that promotes fathers' involvement and strengthens the families' discussion on child growth is needed to improve GMP service utilization.